(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2014)
This article examines the cultural norms and customs of the Acehnese by analysing their traditional oral prohibitions, or haba ureueng tuha. In Aceh, cultural prohibitions are used to indirectly teach children cultural norms and manners. These prohibitions are typically followed by threats of misfortune or supernatural warnings. Because few studies of Acehnese cultural prohibitions exist in the literature, this article reports specifically on the role of mystical threats in some Acehnese prohibitions. By conducting interviews with 100 informants, 19 prohibitions containing mystical threats were collected. These threats were further categorised into four groups: black magic, evil spirits, ghouls and sunset-related prohibitions. Mystical threats were traditionally used to draw attention to forbidden behaviour. However, the use of mystical threats is changing; as education levels rise and the use of communication technologies increases, the basis for mystical threats is being challenged. This research found that although most modern Acehnese people do not strictly believe the mystical threats attached to the prohibitions, these prohibitions are still used to teach people how to behave virtuously and in accordance with their beliefs and traditions.